A hybrid algorithm for speckle noise reduction of ultrasound images. (September 2017) - Singh, Karamjeet; Ranade, Sukhjeet Kaur; Singh, Chandan
Highlights: A hybrid speckle noise reduction algorithm is proposed. It combines the advantages of Guided, Bilateral and rotation invariant NLM. Achieve an optimal balance between speckle noise reduction and feature preservation by proposed hybrid algorithm. The hybrid algorithm provides excellent denoising performance on synthetic, simulated and real US images. Experimental results prove that the hybrid algorithm have better denoising capability than recently proposed speckle noise reduction filters. Abstract: Background and objective: Medical images are contaminated by multiplicative speckle noise which significantly reduce the contrast of ultrasound images and creates a negative effect on various image interpretation tasks. In this paper, we proposed a hybrid denoising approach which collaborate the both local and nonlocal information in an efficient manner. The proposed hybrid algorithm consist of three stages in which at first stage the use of local statistics in the form of guided filter is used to reduce the effect of speckle noise initially. Then, an improved speckle reducing bilateral filter (SRBF) is developed to further reduce the speckle noise from the medical images. Finally, to reconstruct the diffused edges we have used the efficient post-processing technique which jointly considered the advantages of both bilateral and nonlocal mean (NLM) filter for the attenuation of speckle noise efficiently. Methods: The performance of proposed hybrid algorithm is evaluated on synthetic, simulated and real ultrasound images. The experiments conducted on various test images demonstrate that our proposed hybrid approach outperforms the various traditional speckle reduction approaches included recently proposed NLM and optimized Bayesian-based NLM. Results: The results of various quantitative, qualitative measures and by visual inspection of denoise synthetic and real ultrasound images demonstrate that the proposed hybrid algorithm have strong denoising capability and able to preserve the fine image details such as edge of a lesion better than previously developed methods for speckle noise reduction. Conclusions: The denoising and edge preserving capability of hybrid algorithm is far better than existing traditional and recently proposed speckle reduction (SR) filters. The success of proposed algorithm would help in building the lay foundation for inventing the hybrid algorithms for denoising of ultrasound images.